Are medical educators in general practice untapped potential to increase training capacity in sexual and reproductive healthcare? Results of a survey in London, UK. Issue 5 (2nd September 2016) - Ma, Richard; Shah, Radhika
Abstract: Background: Long waiting times for training in sexual and reproductive healthcare (SRH) including long acting reversible contraception (LARC) might lead to attrition from training programmes, leading to reduced capacity for sexual health services, and reduced access to such contraception for women. Setting: General practice in London, UK. Question: Can medical educators in general practice be used as untapped potential to train other health care professionals in sexual and reproductive healthcare? Method: We conducted an online survey to find out the qualifications, skills and willingness of established educators in primary care in London to train other clinicians in sexual and reproductive healthcare, including LARC. Results: We received 124 responses from medical educators (10.1% response rate from general practitioner (GP) trainers and 59.0% of clinical supervisors for Foundation Year doctors). 86 (69.9%) had diploma of the Faculty of Sexual and Reproductive Healthcare (DFSRH) qualification and further 18 (14.6%) were interested in obtaining this qualification. Eleven respondents were trained to fit intrauterine contraception only, three for contraceptive implants only and 37 were trained to fit both. 50 (40.3%) of 124 respondents were willing get involved in DFSRH training; 74% of these were willing to teach on any component of DFSRH including LARC. Discussion: There is a shortage of training places and long waiting list for clinicians who wish to train in SRH. This survey suggests there is a pool of GP educators with skills and experience in SRH and are willing to train others. This can potentially increase the training capacity and improve overall access to good contraception and LARC for women.